The equivalent expression of the expression is (x - 1) / 2(x - 4). Then the correct option is C.
What is an equivalent expression?
The equivalent is the expressions that are in different forms but are equal to the same value.
The expressions are given below.
[tex]\rm \dfrac{x + 2}{x^2 - 16} \ and \ \dfrac{2x +4}{x^2 + 3x - 4}[/tex]
Then the division of the expressions will be
[tex]\rm \rightarrow \dfrac{\dfrac{x + 2}{x^2 - 16} }{ \dfrac{2x +4}{x^2 + 3x - 4}} \\\\\\\rightarrow \dfrac{\dfrac{x + 2}{(x- 4 )(x + 4)} }{ \dfrac{2x +4}{(x + 4)(x -1)}}\\\\\\\rightarrow \dfrac{\dfrac{x + 2}{(x- 4 )} }{ \dfrac{2x +4}{(x -1)}}\\\\\\\rightarrow {\dfrac{x + 2}{x- 4 } \times \dfrac{x - 1}{2x +4}}\\\\\\\rightarrow {\dfrac{x - 1}{2(x- 4) }[/tex]
The expression which is equivalent to the given expression is (x - 1) / 2(x - 4). Then the correct option is C.
More about the equivalent link is given below.
https://brainly.com/question/889935
#SPJ1